Progressive Muscle Relaxation: Can it Reduce Competitive Anxiety? - Miftakhul Jannah; Rachman Widohardhono; Navylia Tirta Kencana (OVS LLC, 2023)
The study purpose was to determine the effect of progressive muscle relaxation training on reducing competitive anxiety among shooting athletes. Materials and methods. An experimental approach with a pretest-posttest control group design was used in this study. The experiment was carried out eight times. A total of 12 athletes, 8 males and 4 females, who were shooting athletes, took part in this research. The athletes in this study, who joined the regional training center in East Java Province, Indonesia, ranged in age from 20 to 44 years. In this investigation, saturated samples, including those from all individuals, were used. Data were obtained from competitive anxiety scales during the pre- and post-test periods. Independent samples t-tests were used to assess the data. Results. The t-value for this study is -14,210, and the p-value is 0.001. These findings suggest that progressive muscle relaxation training reduces competitive anxiety in shooting athletes. The athlete's awareness of the value of mental training contributes to reduction in competitive anxiety. This study has gained traction since athletes are aware of the value of preparing for training before competing because they attend and participate in the regional training center. Conclusions. Progressive muscle relaxation training can be used as an intervention to help shooting athletes reduce their competitive anxiety.